EHRA clinical consensus statement on conduction system pacing implantation: endorsed by the Asia Pacific Heart Rhythm Society (APHRS), Canadian Heart Rhythm Society (CHRS), and Latin American Heart Rhythm Society (LAHRS). Issue 4 (15th April 2023) - Burri, Haran; Jastrzebski, Marek; Cano, Óscar; Čurila, Karol; de Pooter, Jan; Huang, Weijian; Israel, Carsten; Joza, Jacqueline; Romero, Jorge; Vernooy, Kevin; Vijayaraman, Pugazhendhi; Whinnett, Zachary; et al.
Abstract: Conduction system pacing (CSP) has emerged as a more physiological alternative to right ventricular pacing and is also being used in selected cases for cardiac resynchronization therapy. His bundle pacing was first introduced over two decades ago and its use has risen over the last five years with the advent of tools which have facilitated implantation. Left bundle branch area pacing is more recent but its adoption is growing fast due to a wider target area and excellent electrical parameters. Nevertheless, as with any intervention, proper technique is a prerequisite for safe and effective delivery of therapy. This document aims to standardize the procedure and to provide a framework for physicians who wish to start CSP implantation, or who wish to improve their technique.